2015
DOI: 10.1038/srep12567
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of IS6110 insertion sites provide a glimpse into genome evolution of Mycobacterium tuberculosis

Abstract: Insertion sequence (IS) 6110 is found at multiple sites in the Mycobacterium tuberculosis genome and displays a high degree of polymorphism with respect to copy number and insertion sites. Therefore, IS6110 is considered to be a useful molecular marker for diagnosis and strain typing of M. tuberculosis. Generally IS6110 elements are identified using experimental methods, useful for analysis of a limited number of isolates. Since short read genome sequences generated using next-generation sequencing (NGS) platf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 55 publications
5
44
0
3
Order By: Relevance
“…The third set of data comes from a collection of sequence reads archives (NCBI-SRA and EMBL-SRA) that has been retrieved from some state-of-the-art articles to represent the diversity of MTC lineages [20, 21]. This collection was completed by SRA queries on the NCBI search engine, with taxid values of 33894 and 78331, corresponding respectively to M. tuberculosis variant africanum and M. canettii organisms.…”
Section: Methodsmentioning
confidence: 99%
“…The third set of data comes from a collection of sequence reads archives (NCBI-SRA and EMBL-SRA) that has been retrieved from some state-of-the-art articles to represent the diversity of MTC lineages [20, 21]. This collection was completed by SRA queries on the NCBI search engine, with taxid values of 33894 and 78331, corresponding respectively to M. tuberculosis variant africanum and M. canettii organisms.…”
Section: Methodsmentioning
confidence: 99%
“…This IS-mediated mechanism, that has been described in previous studies is a general mechanism, i.e. it happens independently of lineage and is the responsible of IS 6110 convergence of IS copy numbers (Roychowdhury, et al, 2015). The final result is the change from x to x-1 copies of IS 6110 , with the loss of all spacers between the two copies.…”
Section: Discussionmentioning
confidence: 88%
“…IS 6110 -RFLP was the golden standard to define epidemiological clusters at the end of the nineties and stayed so during around 20 years, until it was replaced by MIRU-VNTR 1 and more recently by Whole-Genome-Sequencing (Schurch, et al, 2010; Supply, et al, 2006; van Embden, et al, 1993; van Soolingen, et al, 2007) (for a recent review on evolution of TB molecular epidemiological methods, see also (Garcia De Viedma and Perez-Lago, 2018)). Previous results on IS 6110 insertion sites have shown that independent IS 6110 copy acquisition through transposition into hot-spots was a common mechanism explaining convergence in IS 6110 copy number in some of the MTBC sublineages (Dale, et al, 2003; Roychowdhury, et al, 2015). A recent paper on the micro- and macro-evolution of Lineage 2 of MTC in relation to IS 6110 transposition also stress the interest of such studies using WGS (Shitikov, et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…The insertion sequence IS6110 has been extensively used as a MTBC-specific marker since first described in 1990[8]. In addition, the IS6110 can be present in high copy numbers in some MTBC strains (from 0 to 27 copies)[9], causing the nucleic acid amplification tests (NAAT) targeting this sequence to achieve higher sensitivities for strains carrying several copies. However, the specificity of the IS6110 has been questioned since two decades ago[1015] what, along with the fact that some strains lack this insertion sequence, can lead to an incorrect diagnosis[16,17].…”
Section: Introductionmentioning
confidence: 99%